THE CONCEPT OF ‘SHARING’ IN CHINESE SOCIAL MEDIA - Zhao, Luolin; John, Nicholas (AoIR Selected Papers of Internet Research, 2019)
In this paper we analyze the concepts of fenxiang and gongxiang—the Mandarin words for ‘sharing’—in the context of Chinese social media. Drawing on earlier work on ‘sharing’, and based on analyses of four corpuses and changes over time to the homepages of 32 Chinese social network sites (accessed through the Wayback Machine), we find that the concepts of fenxiang and gongxiang offer a heuristic for understanding Chinese social media, while also pointing to an important facet of the discursive construction of Chinese social media. Although seeming to refer to the same activities as ‘sharing’, analysis of the language of fenxiang and gongxiang in Chinese social media reveals the entanglement of a new individualistic self with a self that remains socially embedded in pre-existing relationships; it shows how micro-level harmony (fenxiang) and macro-level harmony (gongxiang) cohere with each other; while also reflecting the interplay among social media platforms, users, and the state.